Pharmacokinetics of single oral dose trazodone: a randomized, two-period, cross-over trial in healthy, adult, human volunteers under fed condition - Kale, Prashant; Agrawal, Yadvendra K. (Frontiers in Pharmacology, 2015)
Objective To assess the bioequivalence of single dose trazodone hydrochloride USP 100 mg tablets administered as an oral dose under fed condition. Methods This study was an open-label, balanced, randomized, two-sequence, two-treatment, two-period, single oral dose, crossover bioequivalence study in healthy, adult, human subjects under fed conditions. After an overnight fast of at least 10 hours, the subjects were served a high fat and high calorie vegetarian breakfast, which they were required to consume within 30 minutes. A single oral dose (100 mg) of either the test or the reference product was administered to the subjects. The primary pharmacokinetic parameters, maximum plasma concentration (Cmax) and area under the plasma concentration–time curve (AUC) from time zero to last measurable concentration (AUC0-t) and extrapolated to infinity (AUC0-) were compared by an analysis of variance using log-transformed data. Bioequivalence was concluded if the 90% confidence intervals (CIs) of the adjusted geometric mean (gMean) ratios for Cmax and AUC were within the predetermined range of 80%-125%, in accordance with regulatory requirements. Results For the test formulation, the trazodone gMean Cmax was 1480.9 ng/mL (vs. 1520.2 ng/mL for reference), AUC0-t was 18193.0 ng·h/mL (vs. 18209.8 ng·h/mL) and AUC0- was 19346.3 ng·h/mL (vs. 19393.4 ng·h/mL). The 90% CIs for the ratio (test/reference) were 93.0-102.0% for Cmax, 96.7-103.2% for AUC0-t and 96.1-103.5% for AUC0-. There were no deaths or serious adverse events during the conduct of the study. Conclusion Test product when compared with the Reference product meets the bioequivalence criteria with respect to the rate and extent of absorption of Trazodone under fed condition.